2018
DOI: 10.4236/as.2018.92015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet Supplementation with Combinations of Soybean and Linseed Oils on Milk Production and Fatty Acid Profile in Lactating Dairy Ewes

Abstract: Thirty-six Pampinta ewes were used in a completely randomized design to examine the effectiveness of soybean (SO) and linseed (LO) oils to reduce the concentration of the atherogenic fatty acids (FA) of milk (C12:0 to C16:0) and increase the content of conjugated linoleic (cis-9, trans-11 C18:2) also called rumenic acid (RA) and vaccenic acids (trans-11C18:1, VA). Six ewes per treatment received a Control diet alone (71% alfalfa hay and 29% concentrate) or supplemented (0.24 kg/ewe·day) with pure oils (SO100 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Although both of n-3 and n-6 FA are essential and have valuable impacts on human health, excessive levels of n-6 FA and very low levels of n-3 FA (increased n-6 to n-3 ratio) possibly interfering the way of the body to utilize n-3 FA and therefore limit their abundant health benefits (Simopoulos, 2016). LO supplementation could lower the ratio of n-6 to n-3 more than SO supplementation (Antonacci et al, 2018). The ratio of n6 to n-3 is desirable to be closer to 2:1 (Benbrook et al, 2013).…”
Section: Milk Fatty Acid Profilementioning
confidence: 99%
“…Although both of n-3 and n-6 FA are essential and have valuable impacts on human health, excessive levels of n-6 FA and very low levels of n-3 FA (increased n-6 to n-3 ratio) possibly interfering the way of the body to utilize n-3 FA and therefore limit their abundant health benefits (Simopoulos, 2016). LO supplementation could lower the ratio of n-6 to n-3 more than SO supplementation (Antonacci et al, 2018). The ratio of n6 to n-3 is desirable to be closer to 2:1 (Benbrook et al, 2013).…”
Section: Milk Fatty Acid Profilementioning
confidence: 99%
“…"It is therefore expected that a diet with vegetable oils rich in unsaturated fatty acids and secondary fatty components could not only improve the nutritional properties (fatty acid profile) but could also improve the physical properties of milk" [7]. "The most significant changes in milk fat quality relate to rheological (melting) properties, which influence numerous quality aspects of manufactured dairy products.…”
Section: Introductionmentioning
confidence: 99%
“…Shazly et al [11] observed that "the physical properties of anhydrous milk fat (AMF) such as sold fat content (SFC) of cows and buffaloes supplemented with flaxseed oil (FO), soybean oil (SO), or their mixture (FSO) were affected not only by its content of USFA but also by its contents of lipid-minor components such as cholesterol and vitamin E". Antonacci et al [7] reported that "the soybean-linseed oil blend at 50% resulted in the highest number of favorable nutritional changes in ewe's milk including the decrease in the hypercholesterolemic fraction of milk, the simultaneous increase in vaccenic, rumenic and linolenic acids, the n-6/n-3 ratio lower than 4 and a low atherogenic index". In another study, Lin et al [12] reported "a decrease in the hardness and solid fat index (SFI) of milk fat derived from the cows supplemented with calcium salts of oleic acid and this was also attributed to an increase in monounsaturated fatty acids and a decrease in saturated fatty acids".…”
Section: Introductionmentioning
confidence: 99%
“…Production of these isomers in the rumen is enhanced as linoleic acid intake increases, indicating the ability of microbes to hydrogenate can be overcome by high levels of unsaturated fatty acids (Loor, Quinlan, Bandara, & Herbein, 2002). Antonacci, Bussetti, Rodriguez, Cano, & Gagliostro (2018) reported that the soybean-linseed oil blend at 50% resulted in the highest number of favorable nutritional changes in ewe's milk taking into account the decrease in the hypercholesterolemic fraction of milk, the simultaneous increase in vaccenic, rumenic and linolenic acids, the n-6/n-3 ratio lower than 4 and a low atherogenic index. Therefore, it can be expected that a diet with vegetable oils rich in unsaturated fatty acids and secondary fatty components could not only improve the nutritional properties (fatty acid profile) but could also improve the physical properties of milk.…”
Section: Introductionmentioning
confidence: 99%